\(\dfrac{1}{4}+\dfrac{1}{4^2}+\dfrac{1}{4^3}+\dfrac{1}{4^4}+\dfrac{1}{4^5}+\dfr...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 10 2021

\(S=\dfrac{1}{4}+\dfrac{1}{4^2}+\dfrac{1}{4^3}+...+\dfrac{1}{4^{30}}\)

\(\Rightarrow4S=1+\dfrac{1}{4}+\dfrac{1}{4^2}+...+\dfrac{1}{4^{29}}\)

\(\Rightarrow3S=4S-S=1+\dfrac{1}{4}+\dfrac{1}{4^2}+...+\dfrac{1}{4^{29}}-\dfrac{1}{4}-\dfrac{1}{4^2}-...-\dfrac{1}{4^{30}}=1-\dfrac{1}{4^{30}}\)

\(\Rightarrow S=\dfrac{1-\dfrac{1}{4^{30}}}{3}\)

11 tháng 7 2017

a) \(\dfrac{-2}{3}+\dfrac{3}{4}-\dfrac{-1}{6}+\dfrac{-2}{5}=\dfrac{1}{12}-\dfrac{-1}{6}+\dfrac{-2}{5}=\dfrac{1}{4}+\dfrac{-2}{5}=\dfrac{-3}{20}\)

b) \(\dfrac{-2}{3}+\dfrac{-1}{5}+\dfrac{3}{4}-\dfrac{5}{6}-\dfrac{-7}{10}=\left(\dfrac{-2}{3}-\dfrac{5}{6}\right)+\left(\dfrac{-1}{5}-\dfrac{-7}{10}\right)+\dfrac{3}{4}\)

\(=\dfrac{-3}{2}+\dfrac{1}{2}-\dfrac{3}{4}\)

= \(=-1-\dfrac{3}{4}\)

\(=\dfrac{-1}{4}\)

c)\(\dfrac{1}{2}-\dfrac{-2}{5}+\dfrac{1}{3}+\dfrac{5}{7}-\dfrac{-1}{6}+\dfrac{-4}{35}+\dfrac{1}{41}\)

= \(\left(\dfrac{1}{2}-\dfrac{-1}{6}+\dfrac{1}{3}\right)+\left(\dfrac{-4}{35}+\dfrac{5}{7}-\dfrac{-2}{5}\right)+\dfrac{1}{41}\)

= \(1+1+\dfrac{1}{41}\)

= \(\dfrac{83}{41}\)

d)\(\dfrac{1}{100.99}-\dfrac{1}{99.98}-\dfrac{1}{98.97}-...-\dfrac{1}{3.2}-\dfrac{1}{2.1}\)

= \(\dfrac{1}{100}-\dfrac{1}{99}+\dfrac{1}{99}-\dfrac{1}{98}+...+\dfrac{1}{3}-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{1}\)

= \(\dfrac{1}{100}-\dfrac{1}{1}\)

= \(\dfrac{-99}{100}\)

11 tháng 7 2017

d đảo 1/1.2.1/2.3 ... 1/99.1000

=1/1 -1/2 +1/2-1/3 ... -1/99 - 1/1000

=1/1 -1/1000

=999/1000

b: \(\left(\dfrac{2}{5}-\dfrac{7}{10}x\right):\dfrac{5}{3}=-\dfrac{3}{4}\)

\(\Leftrightarrow\dfrac{2}{5}-\dfrac{7}{10}x=\dfrac{-3}{4}\cdot\dfrac{5}{3}=\dfrac{-5}{4}\)

\(\Leftrightarrow x\cdot\dfrac{7}{10}=\dfrac{2}{5}+\dfrac{5}{4}=\dfrac{8+25}{20}=\dfrac{33}{20}\)

\(\Leftrightarrow x=\dfrac{33}{20}:\dfrac{7}{10}=\dfrac{33}{20}\cdot\dfrac{10}{7}=\dfrac{33}{14}\)

c: \(\dfrac{7}{16}:\left(\dfrac{1}{4}x+\dfrac{9}{2}\right)-\dfrac{11}{6}=0\)

\(\Leftrightarrow\dfrac{7}{16}:\left(\dfrac{1}{4}x+\dfrac{9}{2}\right)=\dfrac{11}{6}\)

\(\Leftrightarrow x\cdot\dfrac{1}{4}+\dfrac{9}{2}=\dfrac{11}{6}:\dfrac{7}{16}=\dfrac{88}{21}\)

\(\Leftrightarrow x\cdot\dfrac{1}{4}=\dfrac{88}{21}-\dfrac{9}{2}=-\dfrac{13}{42}\)

hay \(x=-\dfrac{26}{21}\)

27 tháng 7 2017

a, \(\left(0,8.7+0,64\right).\left(1,25.7-\dfrac{4}{5}.1,25\right)\)

\(=6,24.1,25\left(7-\dfrac{4}{5}\right)=7,8.6,2=48,36\)

b, \(\dfrac{1}{4}-\dfrac{\dfrac{1}{4}+\dfrac{1}{9}}{\dfrac{1}{9}}=\dfrac{1}{4}-\dfrac{\dfrac{13}{36}}{\dfrac{1}{9}}=\dfrac{1}{4}-\dfrac{13}{4}=-3\)

c, \(2\dfrac{1}{2}-3,4\left(12\right)-\dfrac{4}{3}+\dfrac{1}{3}.\left(\dfrac{1}{2}+0,5-3\dfrac{1}{2}\right)\)

\(=\dfrac{5}{2}-\dfrac{563}{165}-\dfrac{4}{3}+\dfrac{1}{3}.\left(-\dfrac{5}{2}\right)\)

\(=-\dfrac{301}{330}-\dfrac{4}{3}-\dfrac{5}{6}=-\dfrac{508}{165}\)

Chúc bạn học tốt!!!

25 tháng 12 2017

Tính 1 câu thoy nhé !

\(\dfrac{3}{7}.19\dfrac{1}{3}-\dfrac{3}{7}.33\dfrac{1}{3}\)

= \(\dfrac{3}{7}.\left(19\dfrac{1}{3}-33\dfrac{1}{3}\right)\)

=\(\dfrac{3}{7}.-14=-6\)

a: \(=\left(1+\dfrac{4}{23}-\dfrac{4}{23}\right)+\left(\dfrac{5}{21}+\dfrac{16}{21}\right)+\dfrac{1}{2}\)

\(=1+1+\dfrac{1}{2}=2+\dfrac{1}{2}=\dfrac{5}{2}\)

b: \(=\left(\dfrac{1}{25}+\dfrac{5}{25}+\dfrac{25}{25}\right):\left(\dfrac{1}{25}-\dfrac{5}{25}-\dfrac{25}{25}\right)\)

\(=\dfrac{31}{25}:\dfrac{-29}{25}=\dfrac{-31}{29}\)

c: \(=\dfrac{\dfrac{1}{9}-\dfrac{1}{7}-\dfrac{1}{11}}{\dfrac{4}{9}-\dfrac{4}{7}-\dfrac{4}{11}}+\dfrac{\dfrac{3}{5}-\dfrac{3}{25}-\dfrac{3}{125}-\dfrac{3}{625}}{\dfrac{4}{5}-\dfrac{4}{25}-\dfrac{4}{125}-\dfrac{4}{625}}\)

=1/4+3/4

=1

2 tháng 8 2018

a, 1/3-3/4+3/5+1/4-2/9-1/36+1/15

=(1/3+3/5+1/15)-(3/4-1/4+2/9+1/36)

=1 - 3/4

=1/4

b, 3-1/4+2/3-5-1/3+6/5-6+7/4-3/2

=(3-5-6)-(1/4-7/4)+(2/3-1/3)+(6/5-3/2)

=-8 +3/2 +1/3 -3/10

=-97/15

26 tháng 7 2018

a. = \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}-\dfrac{-3}{8}\right\}\)

= \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}+\dfrac{3}{8}\right\}\)

= \(\dfrac{-1}{24}-\dfrac{5}{8}\)

= \(\dfrac{-2}{3}\)

b. = \(12\dfrac{7}{88}-3\dfrac{5}{11}\)

= \(8\dfrac{5}{8}\)

c. = \(\dfrac{-28}{9}+\dfrac{-413}{9}\)

= \(-49\)

d. = \(\dfrac{8}{35}:\dfrac{2}{11}+\dfrac{-8}{35}:\dfrac{2}{11}\)

= \(\dfrac{2}{11}:\left(\dfrac{8}{35}+\dfrac{-8}{35}\right)\)

= 0